Pituitary corticotroph tumour with adrenocortical cells: A distinct clinicopathologic entity with unique morphology and methylation profile. (9th August 2021) - Hickman, Richard A.; Gionco, John T.; Faust, Phyllis L.; Miller, Michael L.; Bruce, Jeffrey; Page‐Wilson, Gabrielle; Rosenblum, Marc K.; Asa, Sylvia L.
Abstract : We describe a rare TPIT‐positive corticotroph PitNET that is admixed with SF1‐positive adrenocortical cells. This dimorphous population of cells showed no colocalisation between TPIT and SF1 by immunofluorescence, and an adrenocortical choristoma was favoured. Methylation array analysis revealed a novel methylation profile in relation to other pituitary neoplasms.